Respuesta :

[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\[-0.35em] \rule{34em}{0.25pt}[/tex]

[tex]\bf \boxed{2^{2x}=3}~\hspace{7em}4^{4x-3}\implies (2^2)^{4x-3}\implies 2^{2(4x-3)}\implies 2^{8x-6} \\\\\\ 2^{8x}\cdot 2^{-6}\implies \cfrac{2^{8x}}{2^6}\implies \cfrac{2^{4\cdot 2x}}{2^6}\implies \cfrac{(2^{2x})^4}{2^6}\implies \cfrac{(3)^4}{2^6}\implies \cfrac{81}{64}[/tex]

The value of [tex]4^{(4x-3)[/tex] the equation  will be  [tex]\frac{81 }{64}[/tex] .

What is expression ?

Expressions is a finite combination of symbols that is well-formed according to rules that depend on the context.

We have,

[tex]2^{2x} =3[/tex]

And,

[tex]4^{(4x-3)} = 2^{2(4x-3)} =2^{{(8x-6)[/tex]

Now,

We have,

[tex]2^{{(8x-6)[/tex]

Now, Rewrite above expression,

[tex]2^{{(8x-6)\ =\ 2^{8x} *\ 2^{-6}[/tex]

Using the exponent rule,

i.e.

[tex]a^{-n}=\frac{1}{a^{n}}[/tex]

[tex]\ 2^{8x} *\ 2^{-6}[/tex]

[tex]=\frac{2^{8x} }{2^{6}}[/tex]

[tex]=\frac{2^{2x\ *\ 4} }{2^{6}}[/tex]

[tex]=\frac{2^{(2x) 4} }{2^{6}}[/tex]

And,

We have,

[tex]2^{2x} =3[/tex]

So,

Using this , we get,

[tex]=\frac{3^{ 4} }{2^{6}}[/tex]

[tex]=\frac{81 }{64}[/tex]

So,

[tex]4^{(4x-3)}=\frac{81 }{64}[/tex]

Hence, we can say that the value of [tex]4^{(4x-3)[/tex] the equation  will be  [tex]\frac{81 }{64}[/tex] .

To know more about expression click here

https://brainly.com/question/14083225

#SPJ2